Health Effects and Pesticide Perception as Determinants of Pesticide Use : Evidence from Bangladesh - Dasgupta, Susmita; Meisner, Craig; Huq, Mainul (World Bank, Washington, DC, 2012)
In a recent survey of 820 Boro (winter rice), potato, bean, eggplant, cabbage, sugarcane, and mango farmers in Bangladesh, over 47 percent of farmers were found to be overusing pesticides. With only 4 percent of farmers formally trained in pesticide use or handling, and over 87 percent openly admitting to using little or no protective measures while applying pesticides, overuse is potentially a threatening problem to farmer health as well as the environment. To model pesticide overuse, the authors used a 3-equation, trivariate probit framework, with health effects and misperception of pesticide risk as endogenous dummy variables. Health effects (the first equation) were found to be strictly a function of the amount of pesticides used in production, while misperception of pesticide risk (the second equation) was determined by health impairments from pesticides and the toxicity of chemicals used. Pesticide overuse (the third equation) was significantly determined by variation in income, farm ownership, the toxicity of chemicals used, crop composition, and geographical location. The results highlight the necessity for policymakers to design effective and targeted outreach programs that deal specifically with pesticide risk, safe handling, and averting behavior. Ideally, the approach would be participatory in nature to address key informational gaps, as well as increasing a farmers' awareness retention. The results also point to specific crops and locations experiencing a higher prevalence of overuse-bean and eggplant in general-and overall production in the districts of Chapainawabganj, Chittagong, Comilla, Jessore, Narshingdi, Rajshahi, and Rangpur. Focusing efforts in these crop and geographical areas may have the most measurable effects on pesticide overuse.